2013
DOI: 10.1038/onc.2013.224
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated regulation of the immunoproteasome subunits by PML/RARα and PU.1 in acute promyelocytic leukemia

Abstract: Recognition and elimination of malignant cells by cytotoxic T lymphocytes depends on antigenic peptides generated by proteasomes. It has been established that impairment of the immunoproteasome subunits, that is, PSMB8, PSMB9 and PSMB10 (PSMBs), is critical for malignant cells to escape immune recognition. We report here the regulatory mechanism of the repression of PU.1-dependent activation of PSMBs by PML/RARα in the pathogenesis of acute promyelocytic leukemia (APL) and the unidentified function of all-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…Comparing chromothripsis-positive (n=13) and -negative (n=14) CK-AML, GEP disclosed a distinct gene signature of 421 significantly differentially expressed genes at a nominal Pvalue <0.05 (the top 200 differentially expressed genes are listed in Online Supplementary Table S1). Among the top most deregulated genes in chromothripsis-positive CK-AML were CCNA1 (-2.9 log fold change, P<0.009; see Online Supplementary Table S1) involved in cell cycle control and proliferation 9 and reflecting our observation of lower bone marrow blast counts in chromothripsis-positive CK-AML, PSMB10 (-1.7 log fold change, P<0.001), known to be critical for immune surveillance, 10 and PIM1 (1.9 log fold change, P<0.002; see Online Supplementary Table S1), encoding a serine threonine kinase involved in FLT3-mediated cell survival, 11 respectively ( Figure 1D). …”
Section: Letters To the Editorsupporting
confidence: 58%
“…Comparing chromothripsis-positive (n=13) and -negative (n=14) CK-AML, GEP disclosed a distinct gene signature of 421 significantly differentially expressed genes at a nominal Pvalue <0.05 (the top 200 differentially expressed genes are listed in Online Supplementary Table S1). Among the top most deregulated genes in chromothripsis-positive CK-AML were CCNA1 (-2.9 log fold change, P<0.009; see Online Supplementary Table S1) involved in cell cycle control and proliferation 9 and reflecting our observation of lower bone marrow blast counts in chromothripsis-positive CK-AML, PSMB10 (-1.7 log fold change, P<0.001), known to be critical for immune surveillance, 10 and PIM1 (1.9 log fold change, P<0.002; see Online Supplementary Table S1), encoding a serine threonine kinase involved in FLT3-mediated cell survival, 11 respectively ( Figure 1D). …”
Section: Letters To the Editorsupporting
confidence: 58%
“…In our study, we observed different changes in LMO2 expression upon ATRA or ATO treatment in NB4 cells (Figure A and B). A similar observation has been found in our previous findings, in which PSMB8 , PSMB9 and PSMB10 show response to ATRA but not ATO . LMO2 expression showed no change or even further down‐regulation in ATRA‐treated NB4 cells (Figure B).…”
Section: Discussionsupporting
confidence: 92%
“…Although Module 1.2 or Cluster-B (in our study) did not include probe sets representing those immunoproteasome genes, the immunoproteasome is regulated by IFN-γ (7072), and therefore, the identification of those genes may have reflected differences in IFN-γ signaling between PR and NP subjects. Furthermore, one Cluster-B gene, PML , has been identified as a regulator of the immunoproteasome (73). Also, the IFN-driven N-PLS-DA confirmed that genes related to the immunoproteasome [i.e., TAP1 (74) and PSMB8 ( LMP7 ) (70)] can be incorporated into the predictive models.…”
Section: Discussionmentioning
confidence: 99%